Penerapan Kultur Campuran Trichoderma reesei dan Aspergillus niger dalam Meningkatkan Kualitas Putak sebagai Pakan (APPLIED MIXED-CULTURED ASPERGILLUS NIGER AND TRICHODERMA REESEI TO INCREASE PUTAK QUALITY AS FEED) - Hilakore, Maritje Aleonor; Suryahadi, Suryahadi; Wiryawan, Komang; Mangunwijaya, Djumali (Jurnal Veteriner, 2019)
Putak is a local feed in west Timor, East Nusa Tenggara Province. It is obtained from soft core of palm tree which is called gebang tree (Corypha gebanga). Putak contains high carbohydrate and fiber but low in protein. As an effort to increase the ptotein level in putak a research was conducted by fermenting it with mixed-cultured of Trichoderma reesei and Aspergillus niger. A laboratorium experimental method was used and arranged factorially in Completely Randomized Design 3 x 4 x 3 namely three inoculant levels of T. reesei (T): 5,0; 7,5 and 10,0 % (w/w), and four levels of A. niger (A) 0,5; 1,0; 1,5 and 2,0% (w/w). Mixed-cultured was done by: first, T.reesei as treatment mix with putak and incubation for two days, after that mix with A.niger, incubation for two days. The best result of this study was on combination of T.reesei 7.5% level and 1,5% of A.niger were crude protein (23.62%) and soluble protein (14.92%) was highest and fiber 10,17%.